Analisis Histopatologis Insang dan Kandungan Logam Berat Pb, Cd dan Fe Pada Ikan Nila (Oreochromis Niloticus) yang Dibudidayakan di Kolam Bekas Tambang Kota Samarinda - Sudrajat Sudrajat; Dwi Astuti; Muhamad Mustakim (Universitas Riau, 2020)
Coal mining activities openly cause the formation of mine pits and are currently used by the community for fish farming. This research aims to determine the histopathological status of gills, heavy metal content (Pb, Cd, and Fe) in tilapia fish (Oreochromis niloticus) and water bodies ponds. Samples were taken by purposive sampling technique at four locations with different ages, namely Senong Pit (5 years), Goldstar Pit (10 years), Bendang Galactic Pit (15 years) and Control. Measuring heavy metal content was carried out using AAS. Fish gills are processed by the paraffin method and hematoxylin-eosin staining. The results of the analysis of the heavy metal content of Pb, Cd, and Fe in surface water in all ponds are below the Class II Water quality standard based on the Provincial Regulation of East Kalimantan No. 02 of 2011. The value of heavy metal concentrations in sediments is higher than in water. Pb content in Tilapia (Oreochromis niloticus) meat from all ponds is between 2.92 to 4.41 mg / kg, while Cd is between 0.02 to 0.03 mg / kg. The Pb metal content status of the results of this study is above the limit of heavy metal contamination determined by BPOM Decree No. 5 of 2018 which is 0.02 mg / kg, while the heavy metal Cd is still below the specified limit of 0.10mg / kg.The total content of Fe metal ions in fish meat is 83.64 up to 144.92 mg/kg bw These results indicate the total content of Fe ions is far above the safe limit standard for the presence of Fe contaminants in all food sources based on FAO / WHO (2011) of 0.8 mg/kg. Fish originating from all post-mining pond ages indicate damage to the histological structure gills which are characterized by damage to epithelial cells, changes in secondary lamella structures characterized by hyperplasia, destruction of secondary lamella structures and filaments, lamella aneurism and secondary lamella fusion. The results showed that histopathologically and bioaccumulation of heavy metals in fish meat from post-mining ponds showed unhealthy conditions.